Experimental and theoretical modelling of kinetic and equilibrium Ba isotope fractionation during calcite and aragonite precipitation. (15th January 2020) - Mavromatis, Vasileios; van Zuilen, Kirsten; Blanchard, Marc; van Zuilen, Mark; Dietzel, Martin; Schott, Jacques
Abstract: Barium isotope fractionation during calcite and aragonite inorganic precipitation was studied in mixed flow reactors as a function of precipitation rate at 25 °C and pH = 6.3 ± 0.1. The measured Ba isotope fractionation that occurs between calcite and the forming fluid in the investigated range of calcite growth rates (10 -8.0  ≤  R p(calcite)  ≤ 10 −7.3  mol/m 2 /s) is insignificant. Barium isotope fractionation between aragonite and the fluid decreases with increasing precipitation rate from Δ 137/134 Baaragonite-fluid  = +0.25 ± 0.06‰ for R p(aragonite)  ≤ 10 −8.7  mol/m 2 /s to −0.10 ± 0.08‰ for R p(aragonite)  = 10 −7.6  mol/m 2 /s, thus reflecting preferential incorporation of either heavy or light Ba isotopes in aragonite at slow and fast growth rates, respectively. The dependence of Ba isotope fractionation on aragonite growth rate is well described by the surface reaction kinetic model developed by DePaolo (2011) when the values +0.27‰ and −2.0 ± 0.2‰ are used for the equilibrium and kinetic Ba isotope fractionation factor, respectively. The enrichment of aragonite in the heavier Ba isotopes is consistent with the equilibrium fractionation factor of +0.34‰, calculated here between Ba-substituted aragonite and Ba 2+ (aq), from first-principles calculations. This positive fractionation is related to a shorter average BaO bond length in the aragonite structure while the coordination number does not change much (i.e. 9). The lack of isotope fractionation between the Ba aquo ions and the 6-coordinated Ba in calcite likely suggests that the coordination reduction required for the incorporation in the lattice of Ba adsorbed at calcite growing sites proceeds without isotope fractionation with the fluid. Otherwise the precipitated calcite should have been enriched in heavy isotopes by ∼0.17‰, as predicted by first-principles calculations. These results are the first experimental measurements of Ba isotope fractionation during inorganic calcite and aragonite mineral formation and set the basis for understanding the mechanisms controlling Ba isotope composition in CaCO3 minerals that is an essential perquisite for application of this isotopic system in natural samples.